Iowa Birdline update, August 20-21, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for August 20-21, 1990. Highlights of the update were the numerous reports of several species of shorebirds, waders, and Warblers. Also of note were sightings of a Ruddy Turnstone, Buff-breasted Sandpipers, Little Blue Herons, Carolina Wrens, and Blue-gray Gnatcatchers. Epson - sheet feed/flatbed